Juno/JIRAM: Planning and commanding activities. Issue 1 (1st January 2020) - Noschese, R.; Cicchetti, A.; Sordini, R.; Cartacci, M.; Mura, A.; Brooks, S.; Lastri, M.; Filacchione, G.; Migliorini, A.; Moriconi, M.L.; Adriani, A.; Becker, H.N.; et al.
Highlights: We describe the in detail the activities of planning and commanding for JIRAM. We describe the observation strategy to construct robust observation timelines. We describe the timing of JIRAM science observation. Abstract: In the context of space missions, where science is the most important goal, careful planning and detailed commanding are fundamental. The planning and commanding phases are activities whose complexity depends on the instrument characteristics, environmental constraints and scientific goals. The purpose of this work is to describe in detail these activities for the Jovian Infrared Auroral Mapper (JIRAM) on board the Juno spacecraft, a NASA mission to Jupiter. To maximize the scientific return, we fully employ the flexibility offered by the JIRAM operational modes to efficiently plan observations of various Jovian targets, in spite of the harsh Jovian radiation environment and the spinning state of the Juno spacecraft. Moreover, the JIRAM observations are limited by the challenging pointing and timing scheme of the mission, which impose constraints on both the observation planning and instrumental commanding.